Neurotransmitter dysfunction and atrophy of the caudate nucleus in Alzheimer's disease. - Pearce, B; Palmer, A; Bowen, D; Wilcock, G; Esiri, M; Davison, A (1984)
The caudate nucleus from examples of Alzheimer's disease (mean age 68, range 51-77 yr) had a mean wet weight and total protein content that were significantly lower than control. Biochemical markers of various specific nerve cells were determined. These are thought to reflect intrinsic cholinergic neurones (choline acetyltransferase activity) and corticostriatal (L-[3H]glutamate binding), nigrostriatal (dopamine and homovanillate concentrations), and ascending brain stem (serotonin, 5-hydroxyindoleacetate, and noradrenaline concentrations) tracts. There is evidence of selective vulnerability, with cholinergic, dopaminergic, and possibly glutamergic neurons being affected, but not serotonergic and noradrenergic cells. Dopaminergic neurons are probably not markedly reduced in number, but may not be fully operating. Some observations made for the monoamines, as well as the alteration in L-[3H]glutamate binding, seem to lay emphasis on the importance of cortical pathology in Alzheimer's disease.